The impact of French occupation on Egypt (1798-1801): a reassesment - Wan Kamal Mujani; Napisah Karimah Hj. Ismail (Universiti Kebangsaan Malaysia, 2010)
The aim of this article is to reassess how far the remarks that ‘the French occupation on Egypt (1798-1801) had brought massive reformation from political, economic and social aspects and at the same time it also gave many positive effects until the country started its process of modernization.’ We view that such statement should be reviewed since there are still many writers support such incorrect ideas which were not supported by historical facts. The history proves that the French was not sucessful in bringing the reformation to Egypt from political, economic and social aspects. Moreover, their invasion caused more negative effects compared to the positive effects. Politically, eventhough the Egyptians were exposed to the idea of democracy and parliamentary by the establishment of several Diwans (House of Representatives), in reality they were not in power because the true power was completely in the hand of French. From the the economic aspect on the other hand, the French did not succeed in bringing the development in trade, agriculture and industry because of the recurrent political unrests and the imposition of heavy taxes which gave bad effects to the people. Meanwhile, from the social aspect, most of the reformations in knowledge, education, technology etc were also done for sake of French. The real changes and reformations in Egypt only occurred after the retreat of French i.e during the reign of Muhammad ‘Ali Pasha (1805-1849) who developed Egypt on all the three main aspects of politics, economics and social which finally brought the positive effects to the development of the country.